Financial Inclusion of Rural Households – A Case Study from Hanumangarh District, Rajasthan - Bhatia, Anju; Saraswat, Neetu (Indian Journal of Extension Education, 2011)
Financial inclusion refers to accessibility of financial services to people of all walks of life at an affordable cost. The interest has been increased in financial inclusion in recent years after globalisation and economic reforms. Indian economy is growing at very fast pace, as majority of population lives in rural area, the financial inclusion of rural households is very important. In this background, the present study was carried out. The objectives of the study were to determine the extent of financial inclusion of rural households and also to find out the correlation between financial inclusion and socio-economic status of rural households. The sample consisted of 211 rural households from the purposively selected Goluwala village of the district. Pre-validated and pre-tested semi-structured interview schedules were used to collect the data. The findings showed that 63 per cent of households were having bank account. The use of financial services was limited to having a saving account in the bank. In majority of the cases, there was one account per household. Out of the total accounts, two-third accounts belonged to men and remaining one-third belonged to women. The usage of other financial services was limited to less than one fifth of households. There was a low degree of positive correlation between socio-economic status and financial inclusion of rural households. In conclusion, no doubt it is one step forward in the right direction but more innovative strategies need to be adopted to bring the rural households under the umbrella of financial services to reap the benefit of prevailing high growth rate of the country.